Annealing Effect of ZnO Seed Layer on Enhancing Photocatalytic Activity of ZnO/TiO2 Nanostructure - Woo-Young Kim; Soon-Wook Kim; Dae-Hwang Yoo; Eui Jung Kim; Sung Hong Hahn (International Journal of Photoenergy)
Zinc oxide (ZnO)/titanium dioxide (TiO2) nanorods have been synthesized via a hydrothermal method for ZnO nanorods and an electron-beam deposition for TiO2 nanorods. This work examined the effect of annealing ZnO seed layer on the photocatalytic activity of the ZnO/TiO2 nanorods which was determined from photodecomposition of methylene blue under UV irradiation. The photocatalytic activity of the ZnO/TiO2 nanorods was improved with increasing annealing temperature of the seed layer from 300°C to 500°C. Annealing the seed layer at 500°C showed the best photocatalytic activity resulting from high UV absorption ability, a large surface area with flower structure and copious oxygen defects which promote separation of electron-hole pairs reducing electron recombination. The prepared nanorods were characterized by field emission-scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), photoluminescence (PL), and UV-visible spectroscopy.